Effectiveness of Acupressure and William Flexion Exercise on Reducing the Intensity of Mental Pain in Adolescent Women at Guna Bangsa Vocational School, Banjarsari, Lebak, Banten - Nur Anita; Dini Resha Oktavia (STIKep PPNI Jawa Barat, 2023)
Aims: Dysmenorrhea is pain or cramps in the lower abdomen that appear before or during menstruation. The problem of menstrual pain in young women if not addressed immediately can have a bad impact on adolescent productivity including learning activities. Data from the Lebak Regency Health Office in 2021 reported dysmenorrhea cases in adolescents by 62.4% of the 5,000 adolescents surveyed and 35% of them complained that their activity was limited due to dysmenorrhea. Method: The research method uses quasi-experiments with a pre-posttest two group design. Sample of this study was 30 young women in grades X, XI, XII who experienced dysmenorrhea with sampling technique uses total sampling. Instruments use questionnaires. Bivariate analysis uses the paired t-test and independent t-test. Results: The average dysmenorrhea intensity of young women in the intervention group before being given acupressure massage was 6.60 and after being given acupressure massage decreased to 2.80, while in the control group before being given physical movement william's flexion exercise was 6.53 and after being given acupressure massage decreased to 3.87. The results of statistical tests showed that there was an effectiveness of acupressure and william flexion exercise against reducing the intensity of dysmenorrhea in young women (p = 0.000). Conclusion : Acupressure massage is more effective at reducing the intensity of dysmenorrhea compared to giving William's flexion exercise. It is hoped that young women will treat dysmenorrhea in a non-pharmacological way, namely by acupressure massage or doing physical movements in William's flexion exercise.